Developing Personal and Social Responsibility: A Survey of Post-Pandemic Offline Physical Education Learning at SMP Negeri 2 Megamendung - Muhammad Aden Saleh Anggoro; Firman Septiadi; Wening Nugraheni (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
The Covid-19 pandemic that hit Indonesia had a significant impact on the education sector, so schools were forced to carry out distance learning (online). In the implementation of face-to-face learning (offline), there are still many students who show a low level of responsibility, especially in participating in the PJOK learning process. This study aims to determine the level of student responsibility in post-Covid-19 pandemic offline PJOK learning at SMP Negeri 2 Megamendung, which uses the Teaching Personal And Social Responsibility (TPSR) model. This research uses quantitative descriptive method. The study population amounted to 348 students in class VIII, with a research sample of 160 students selected using random sampling technique. The research instrument used was the responsibility observation format. The results showed that most of the VIII grade students at SMP Negeri 2 Megamendung had a high level of responsibility in learning PJOK. Students with high responsibility amounted to 65 students (40.6%), students with moderate responsibility amounted to 30 students (18.7%), and students with low responsibility amounted to 64 students (40%). From these results, it can be concluded that most students show high responsibility in learning PJOK at the school.